Molybdenum Sulfide (MoS2)/Ordered Mesoporous Carbon (OMC) Tubular Mesochannel Photocatalyst for Enhanced Photocatalytic Oxidation for Removal of Volatile Organic Compounds (VOCs) - He, Li; Guan, Wei; Zeng, Yao; Zhao, De; Qiu, Xuemin; Jia, Guo (Frontiers in Chemistry, 2022)
Abstract: Air pollutants have caused severe problems in urban areas, specifically in terms of toxicological impacts on human health. Therefore, it is urgent to develop an effective, safe, and inexpensive technique to remove this air pollutants. In this study, the MoS2/OMC heterojunction photocatalyst was successfully synthesized by a hydrothermal process and used for improving photocatalytic oxidation performance for removing VOCs. Formaldehyde acted as model VOCs in gas phase and removed at room temperature under visible light irradiation. For my research, the microstructure and morphology of the photocatalyst were deeply characterized and the results indicated that MoS2 were successfully coupled into OMC materials to prepare the MoS2/OMC heterojunction photocatalyst. The trend of photocatalytic efficiency for formaldehyde decomposition was MoS2/OMC > MoS2 > OMC. Besieds, the MoS2/OMC heterojunction photocatalyst showed an excellent regeneration performance after several recycles, indicating the potential of MoS2/OMC composite as a promising photocatalyst for VOCs removal. These results indicated that the photocatalytic reactor containing MoS2/OMC photocatalyst was highly active and stable.